2009
DOI: 10.1007/s10661-009-1055-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in water, suspended matter, and sediment from Gökova Bay, Turkey

Abstract: The contents of heavy metals (Fe, Mn, Pb, Cu, Cd, and Hg) dissolved in water and suspended solids of Gökova Bay--partly and fully sampled in 2005 and 2006, respectively--are quite higher than the average values encountered in uncontaminated sea water. The high concentrations are associated with terrestrial inputs from the mining zones and anthropogenic (domestic+industrial) sources. Moreover, the distribution of Fe and Cu is affected by primary production because these elements function as nutrients in biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 14 publications
(17 reference statements)
1
9
2
1
Order By: Relevance
“…Iron (Fe) was ranged between 737-2385 mg/kg (Table III). The maximum value was recorded 2385 mg/kg in polluted area during monsoon lower than the concentration was found by Balkis et al (2010) from Gokova Bay, Turkey. The lowest amount was 737 mg/kg found during monsoon season at the polluted site (Table III).…”
Section: Resultscontrasting
confidence: 59%
“…Iron (Fe) was ranged between 737-2385 mg/kg (Table III). The maximum value was recorded 2385 mg/kg in polluted area during monsoon lower than the concentration was found by Balkis et al (2010) from Gokova Bay, Turkey. The lowest amount was 737 mg/kg found during monsoon season at the polluted site (Table III).…”
Section: Resultscontrasting
confidence: 59%
“…Seasonal distribution of all the heavy metals in the water showed statistically significant difference (p<0.05). (Sklodowski et al 2006;Balkis et al 2010). In this study, as shown in Figure 3; when suspended solid matter increased, the amount of heavy metal in the root, stem and leaf decreased, or vice versa.…”
Section: Resultssupporting
confidence: 52%
“…Previous studies on the RR [6,7] provided general baseline information and attempted to explain the possible effects of industrial discharges on the aquatic environment. Most metals are retained by the particle surfaces and are preferentially transported, deposited, and eventually buried with fine-grained sediments [12]. Nonetheless, rapid expansion of human activity has continuously accelerated the risk of environmental pollution with heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various pollutants, heavy metals are the most toxic, persistent, and abundant, being able to increase their concentration through biomagnification in aquatic habitats [9][10][11]. Most metals are retained by the particle surfaces and are preferentially transported, deposited, and eventually buried with fine-grained sediments [12].…”
Section: Introductionmentioning
confidence: 99%